Retrospective Study of Corneal Transplants in the State of Alagoas - Tonhá, Carolina Dourado Cardoso; Santos, Andréa Maria Cavalcante; Souza, Janaína Christina Norberto de; Muniz, Marcella Cristina Halliday (Brazilian Journal of Transplantation, 2010)
Purpose: To identify profile of patients undergoing corneal transplantation in the State of Alagoas, analyzing the gender, age and ophthalmic history. To assess the reasons for the indications, surgical techniques and intraoperative complications of patients. Methods: Retrospective analysis of 176 medical records at the Eye Bank of the State of Alagoas located in the University Hospital Alberto Antunes - Maceió / AL along the October 2004 to December 2009 period. Results: 176 records were analyzed, and the age of the sampling ranged from 27 days old to 94 years old. There was a slight prevalence of females (51.7%). Main indication to penetrating keratoplasty was bullous keratopathy (31%), followed by leucoma, keratoconus and cornea perforation. Eighty-one eyes had previous surgical history. There were 13 cases of intraoperative complications. Conclusions: This study has allowed understanding the profile of transplant patients in our hospital. The mean age of transplanted patients was 42 years, with slightly higher prevalence of females. Visual indication was the most common, and mostly of elective surgeries. The main indication for penetrating keratoplasty was bullous keratopathy.